COMPUTATIONAL AND POLAROGRAPHIC STUDY ON DRUG-RECEPTOR INTERACTION FOR CARVEDILOL - Adnanhatem, Oraas; Suhail, Falah Shareef Abed; Juda, Amer Mousa (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The aim of this study was to evaluate Carvedilol-receptor binding using computational and polarographic methods. Methods: Differential pulse polarographic (DPP) wave was measured for carvedilol, serine, and aspartic acid in phosphate buffer solution pH 7.4at 37 °C. Interaction of drug receptors with two amino acids serine and aspartic acid was studied by linking the thermodynamic (Keq) and kinetic behavior. The forward reaction rate constant (k1) and reverse reaction rate constant (k-1) was calculated for carvedilol–receptor complexes and through the half-life time was also calculated. Results: The study found that carvedilol, serine and aspartic acid electrical active agents and have E 1/2 0.148, 0.127 and 0.119 V respectively. After formation of drug-receptor molecular complexes, a negative displacement in carvedilol half-wave potential value. Gibbs, free energy was calculated and found to be a negative value for all the molecular complexes indicate that spontaneous interaction occurred. The chemical affinity was also calculated which gave a positive result and indicated a high tendency of molecules to associate with each other. A computational study using the Gaussian software, DFT-6311G on carvedilol-receptor molecular complexes gave significant agreement of complex behavior in the theoretical study with the polarographic study, depending on the values of the energy gap between HOMO-LUMO. Conclusion: the study showed that there is a good rapprochement between theoretical and experimental results allows the possibility of evaluated drug–receptor interaction in Subsequent studies theoretically, also showed the possibility to determine the spontaneously and chemical affinity of drug-receptor molecular complex formation based on polarographic results